(untitled) (Research, Society and Development, 2024)
Introduction: The impaction of maxillary canines is a frequent occurrence, especially in the palatal region, even when there is sufficient space for their alignment in the dental arch. It can be caused by general or local factors, and its diagnosis should be made through clinical, radiographic and tomographic examinations. Aim: The aim of this study was to describe a clinical case of an impacted canine that had previously been unsuccessfully attempted to be orthodontically pulled. Clinical case report: A 19-year-old female patient was referred for extraction of an impacted element 13 on the palate, after attempted traction for two years, carried out as a prophylactic measure against resorption of adjacent dental elements. Careful removal was carried out with the aid of blood products for a better post-operative prognosis. Conclusion: Early diagnosis of dental inclusions is important to enable traction and prevent loss of units. However, when the inclusion does not allow the tooth to be used, it is important to remove it in a less invasive way and with the better possible post-operative outcome for the patient.